2016
DOI: 10.3892/mmr.2016.5570
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol inhibits IL-1β-induced inflammation in orbital fibroblasts through the suppression of NF-κB activity

Abstract: Graves' disease is an autoimmune disease of the thyroid gland, which is characterized by hyperthyroidism, diffuse goiter and Graves' ophthalmopathy (GO). Although several therapeutic strategies for the treatment of GO have been developed, the effectiveness and the safety profile of these therapies remain to be fully elucidated. Therefore, examination of novel GO therapies remains an urgent requirement. Celastrol, a triterpenoid isolated from traditional Chinese medicine, is a promising drug for the treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 44 publications
2
24
0
1
Order By: Relevance
“…In the present study, our results displayed that celastrol treatment significantly decreased mRNA and protein expression of TNF-α and IL-1β in myocardial cells in the condition of H/R. These results are consistent with results of other studies founding that celastrol reduced TNF-β in lung infiltration model and inhibited IL-1β-induced inflammation in orbital fibroblasts ( 25 , 26 ). Therefore, we suggested that celastrol attenuated MIRI by relieving TNF-α- and IL-1β-mediated inflammatory damage to cardiomyocytes.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, our results displayed that celastrol treatment significantly decreased mRNA and protein expression of TNF-α and IL-1β in myocardial cells in the condition of H/R. These results are consistent with results of other studies founding that celastrol reduced TNF-β in lung infiltration model and inhibited IL-1β-induced inflammation in orbital fibroblasts ( 25 , 26 ). Therefore, we suggested that celastrol attenuated MIRI by relieving TNF-α- and IL-1β-mediated inflammatory damage to cardiomyocytes.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, Celastrol displays considerable anti-inflammatory activity (De Seabra Rodrigues Dias et al, 2017 ; Zhang et al, 2018 ) and can inhibit cellular inflammation by suppressing NLRP3 activity (Yu et al, 2017 ). Celastrol can also inhibit inflammation by inhibiting the expression of interleukin (IL)-1β (Li et al, 2016b ). Although the anti-inflammatory effects of Celastrol have been studied in many diseases, there are no reports of its anti-inflammatory effects or its molecular mechanisms in COPD.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperthyroidism patients who met the surgical indications were enrolled in the study. Diagnostic criteria for hyperthyroidism or clinical manifestations of patients with hyperthyroidism were: Hyperphagia, intolerance of heat, palpitations, agitation and other high metabolic syndrome, exophthalmos and varying degrees of goiter ( 6 – 8 ), laboratory tests show high levels of free triiodothyronine FT3 or free thyroid hormone FT4, decreased thyroid hormone TSH levels and anti-thyroid antibody-positive. Indications for surgical treatment for hyperthyroidism: Long-term use of drugs with poor results; secondary hyperthyroidism caused by other factors, moderate or beyond primary hyperthyroidism; hyperthyroidism with oppression; recurrence after drug treatment; bone marrow suppression and other toxic response.…”
Section: Methodsmentioning
confidence: 99%